Change of oral microbiome diversity by smoking across different age groups - Seo, Kang; Min, Jin-Young; Min, Kyoung-Bok; Oh, Kun-Hee; Ryoo, Seung-Woo; Son, Seok-Yoon; Lee, Ji-Hyeon (Frontiers in Microbiology, 2025)
IntroductionThe oral microbiome, a complex ecosystem linked to both oral and systemic diseases, undergoes compositional and functional changes with aging. Tobacco exposure is a known disruptor of microbial homeostasis, yet its effect on microbial diversity remains inconsistent. Whether agingmodifies the relationship between smoking and the oral microbiome remains unclear. This study aimed to evaluate (1) the association between serum cotinine and oral microbial diversity, (2) whether this association varies by age, and (3) taxonomic shifts that may explain smoking-related dysbiosis.MethodWe analyzed data from 4,387 adults aged 30–69 years in the U.S. National Health and Nutrition Examination Survey 2009–2012. Serumcotinine, an objective biomarker of nicotine exposure, was used as the primary exposure. Oral microbiome diversity was assessed via 16S rRNA gene sequencing of oral rinse samples. Microbial profiles were analyzed using observed amplicon sequence variants and Bray-Curtis. Alpha diversity declined progressively with age, with the most pronounced reduction among current smokers.ResultsSerum cotinine was inversely associated with alpha diversity, particularly in current smokers aged 60–69 years (adjusted β = −0.1081, p = 0.0002). Beta diversity differed significantly by smoking status (PERMANOVA p < 0.0001). Analysis identified 29 genera were associated with serum cotinine: Haemophilus, Neisseria, and Gemella decreased with higher exposure, while Atopobium and Lactobacillus increased. Tobacco exposure is associated with reduced oral microbial diversity, particularly in older adults.DiscussionThis highlights the synergistic impact of aging and smoking on the oral microbiome and underscores the need for age-specific prevention strategies. Prospective studies are warranted to confirm causality and assess the reversibility of smoking-induced dysbiosis.